"String Theory" of c-kitpos Cardiac Cells. Issue 7 (27th March 2015) - Keith, Matthew C.L.; Bolli, Roberto
<x xml:space="preserve">Abstract</x> Although numerous preclinical investigations have consistently demonstrated salubrious effects of c-kitpos cardiac cells administered after myocardial infarction, the mechanism of action remains highly controversial. We and others have found little or no evidence that these cells differentiate into mature functional cardiomyocytes, suggesting paracrine effects. In this review, we propose a new paradigm predicated on a comprehensive analysis of the literature, including studies of cardiac development; we have (facetiously) dubbed this conceptual construct "string theory" of c-kitpos cardiac cells because it reconciles multifarious and sometimes apparently discrepant results. There is strong evidence that, during development, the c-kit receptor is expressed in different pools of cardiac progenitors (some capable of robust cardiomyogenesis and others with little or no contribution to myocytes). Accordingly, c-kit positivity, in itself, does not define the embryonic origins, lineage capabilities, or differentiation capacities of specific cardiac progenitors. C-kitpos cells derived from the first heart field exhibit cardiomyogenic potential during development, but these cells are likely depleted shortly before or after birth. The residual c-kitpos cells found in the adult heart are probably of proepicardial origin, possess a mesenchymal phenotype (resembling bone marrow mesenchymal stem/stromal cells), and are capable of contributing significantly only to nonmyocytic lineages (fibroblasts, smooth muscle cells, and endothelial cells). If these 2 populations (first heart field and proepicardium) express different levels of c-kit, the cardiomyogenic potential of first heart field progenitors might be reconciled with recent results of c-kitpos cell lineage tracing studies. The concept that c-kit expression in the adult heart identifies epicardium-derived, noncardiomyogenic precursors with a mesenchymal phenotype helps to explain the beneficial effects of c-kitpos cell administration to ischemically damaged hearts despite the observed paucity of cardiomyogenic differentiation of these cells.